A new strategy for treating a cotton dyeing wastewater - Integration of physical-chemical and advanced oxidation processes - Carmen S. D. Rodrigues (2014)
New strategies were herein applied for treating a cotton dyeing wastewater: coagulation/flocculation followed by Fenton's oxidation - Approach 1, Fenton process per se - Approach 2, and Fenton followed by coagulation/flocculation - Approach 3, aiming reducing chemicals consumption. Regarding the cost analysis, which is crucial for deciding on the best strategy to implement, it was found that in approach 1 and approach 2 the hydrogen peroxide has a major influence on the total costs as compared to ferrous ion. In approach 3, the total costs are again mostly related to the consumption of reagents in the oxidation stage. The integration of the Fenton's process followed by coagulation/flocculation provided an effluent that meets the discharge limits, with global organic matter removals of 55.6% for COD, 42.7% for BOD5 and 70.4% for DOC, and almost complete colour reduction (99.6%). However, the combined treatment of coagulation/flocculation followed by Fenton's oxidation exhibits also high overall efficiencies (61.7%, 25.8% and 71.2% for COD, BOD5 and DOC removal, respectively, with almost complete decolourisation) but simultaneously smaller operating costs associated with chemicals consumption (0.82 €/m3), putting into evidence the usefulness of the novel strategy implemented: use of the residual dissolved iron employed as coagulant in the first stage as catalyst in the subsequent Fenton's oxidation. Copyright (c) 2014 Inderscience Enterprises Ltd.